A Panacea for Teaching Listening at Islamic Realm: Interactive Video Viewing Technique - Puspitasari, Hesty (JEELS (Journal of English Education and Linguistics Studies), 2016)
This study is designed to solve the classroom problem dealing with the improvement of listening skill of the students of one private Islamic college that also study at pesantren in which they have lack of exposure in learning English. To cater a new way to overcome this issue, a classroom action research focusing on the implementation of interactive video viewing technique was employed. The findings exemplify that the students show better listening achievement after the implementation of second research cycle.